Pattern of use of anti-hypertensive drugs amongst hypertensive patients in a tertiary care hospital: a cross sectional, observational study - Khan, Sharmin; Maiti, Ram N.; Mandal, Sekhar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Hypertension is one of the primary modifiable risk factors for cardiac and renal diseases and is the single most important risk factor for stroke. Despite different guidelines for management of hypertension like Joint National Committee, British Hypertension Society, National Institute for Health and Care Excellence; there are still the clouds of controversy. The objective of the study was to evaluate the prescribing pattern of antihypertensive drugs among the patients attending medicine outpatient department of a tertiary care teaching hospital Methods: A cross-sectional, observational study was conducted in our hospital over a period of six months. Relevant information was collected from medical records of 209 hypertensive patients fulfilling inclusion criteria. The collected data were sorted and analyzed. Results: Out of 209 patients, maximum were of age group of 45-65 years (55.02%). 115 (55.02%) were male and 94 (44.97%) were female. Diabetes mellitus (24.4%) was the most common associated disease with hypertension. Most of the patients had received single antihypertensive drugs (49.28%). Among the monotherapy category calcium channel blocker (82.78%) was the most commonly prescribed antihypertensive drug class followed by angiotensin receptor blocker (36.36%). Amlodipine (81.82%) was the most common among calcium channel blockers. The most frequent fixed drug combination prescribed consisted of amlodipine and atenolol. Most of the drugs were prescribed in generic name (90.9%). Conclusions: The treatment pattern, in general, conformed to standard treatment guidelines.